Bovine gamma delta T cell responses to the intracellular protozoan parasite Theileria parva - Daubenberger, C.A.; Taracha, E.L.N.; Gaidulis, L.; Davis, W.C.; McKeever, Declan J. (1999)
T cells bearing the gamma delta antigen receptor (gamma delta T cells) can constitute up to 50 percent of T cells in the peripheral blood and lymphoid organs of young cattle. We present data showing that gamma delta T cells are involved in immune responses against Theileria parva. Gamma delta T cells isolated from peripheral blood mononuclear cells (PBMC) of T. parva-naive and -immune cattle proliferated in the presence of fixed or unfixed autologous T. parva-infected lymphoblasts (TpL) and heat-stressed concanavalin A (ConA)-induced blasts (ConA blasts) but not untreated ConA blasts. The specificity of response was further evaluated with a panel of gamma delta T-cell receptor, but not by MAbs specific for class I and class II major histocompatibility complex (MHC) molecules. In addition, TpL but not ConA blasts from a variety of MHC-mismatched animals induced proliferation of the gamma delta T-cell lines and clones. these gamma delta T cells were found to respond to TpL infected with several different parasite stocks and failed to recognize TpL after elimination of the parasite by the theilericidal drug BW 720C. Assays for cytotoxic activity of gamma delta T cells sorted from bulk cultures of immune PBMC restimulated several times with autologous TpL demonstrated that effector cells whose specificity is similar to that of proliferating cells are generated. These results suggest that bovine gamma delta T cells are activated by and lyse T. parva-infected cells by recognizing conserved parasite-induced or parasite-derived antigens in an MHC-unrestricted fashion.